Workshop on Youth Mental Health First Aid: Approach to Suicide, Depression, Self-harm and Psychosis - Counselling Department, Faculty of Cognitive Sciences and Human Development (2016)
Four lecturers from Counselling Department, Faculty of Cognitive Sciences and Human Development attended a workshop “Youth Mental Health First Aid: Approach to Suicide, Depression, Self-harm and Psychosis” organised by UNIMAS’s Centre for Disability Studies (CoDS) in collaboration with the Mental Health Association of Sarawak on 14th July 2016. The workshop is conducted by Associate Professor Dr Jenny Martin, a social worker lecturer at RMIT Melbourne. Counselling lecturers, Dr Jamayah Saili, Dr Fatahyah Yahya, Dr Rizal Abu Bakar & Puan Samsiah Jayos signed up for the workshop as they will be teaching Introduction to Mental Health, an elective course open for university wide students this coming semester.